Medicoethnobiology of Musahar Community in Nawalpur District, Nepal - Saru, Bimala Devi; Adhikari, Jagan Nath; Bhattarai, Bishnu Prasad (ZOO-Journal, 2021)
The Musahars are a little-known and backward ethnic group of Nepal and have traditional knowledge of ethnomedicine. They used animals and plants for the treatment of various diseases. This knowledge is vanishing as it is not transferred verbally to the next generation. Hence, this study aimed to document such ethnomedicinal knowledge of the Musahar community by using 60 semi-structured questionnaires. The relative frequency of citation and use value were used to analyze the data. This study recorded 14 species of animals belonging to 12 orders and 14 families for the treatment of 11 different types of ailments. Among them, pigeon was the most commonly used species (UV = 0.27), with 44 used reports by 60 respondents. They treated various ailments, among which respiratory problems were the most commonly treated. Similarly, a total of 54 plant species belonging to 26 orders and 35 families for the treatment of 30 different types of ailments were found. Tulsi was the most common species used (UV = 0.188) with 96 use reports. Plants were commonly used to treat respiratory and integumentary disorders. Ethnomedicinal knowledge was more in the elderly than in the younger generation as they showed an affinity towards modern medicine and modern health services. Hence, this study may help to preserve their traditional ethnomedicinal knowledge before it vanishes.